2019
DOI: 10.1016/j.ecoenv.2018.09.079
|View full text |Cite
|
Sign up to set email alerts
|

Airway microbiome is associated with respiratory functions and responses to ambient particulate matter exposure

Abstract: Background-Ambient particulate matter (PM) exposure has been associated with respiratory function decline in epidemiological studies. We hypothesize that a possible underlying mechanism is the perturbation of airway microbiome by PM exposure. Methods-During October 2016-October 2017, on two human cohorts (n = 115 in total) in Shanghai China, we systematically collected three categories of data (1) respiratory functions, (2)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
50
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(51 citation statements)
references
References 42 publications
(50 reference statements)
1
50
0
Order By: Relevance
“…Alterations in the bacterial dynamic ecosystem can directly influence immune homeostasis and aggravate inflammatory diseases (Rakoff-Nahoum et al, 2004;Pascal et al, 2018). Recent studies have shown that PM 2.5 exposure causes bacterial community dysbiosis and exacerbate disease development (Mariani et al, 2018;Qin et al, 2019;Wang et al, 2019). However, whether PM 2.5 influences respiratory microbiota distribution and facilitates bacterial infection remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Alterations in the bacterial dynamic ecosystem can directly influence immune homeostasis and aggravate inflammatory diseases (Rakoff-Nahoum et al, 2004;Pascal et al, 2018). Recent studies have shown that PM 2.5 exposure causes bacterial community dysbiosis and exacerbate disease development (Mariani et al, 2018;Qin et al, 2019;Wang et al, 2019). However, whether PM 2.5 influences respiratory microbiota distribution and facilitates bacterial infection remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…PM 2.5 exposure is associated with increased all-cause and respiratory mortality, impaired lung function, exacerbations of chronic lung diseases, lung cancer, even Acute Respiratory Distress Syndrome (ARDS) [28][29][30][31][32][33][34]. Some studies have found that PM 2.5 exposure could alter human pharyngeal [18], airways [17] and gut microbiota composition [35] because atmospheric particulate matter commonly carries microbes rich in Firmicutes, Proteobacteria and Bacteroidetes phyla [36]. During our study period, the concentration of PM 2.5 is very high in the week around timepoint D30.…”
Section: The Effects Of Azithromycin On Airway Microbial Interactionsmentioning
confidence: 99%
“…Recent studies in healthy murine show that lung communities clustered signi cantly by various environmental sources (vendors, cages and shipments) [3]. The exposure to elevated levels of PM 2.5 contributes to the change in sputum and pharyngeal microbiota composition, even in the healthy cohort [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…PM 2.5 exposure is associated with increased all-cause and respiratory mortality, impaired lung function, exacerbations of chronic lung diseases, lung cancer, even Acute Respiratory Distress Syndrome (ARDS) [27][28][29][30][31][32][33]. Some studies have found that PM 2.5 exposure could alter human pharyngeal [18], airways [17] and gut microbiota composition [34] because atmospheric particulate matter commonly carries microbes rich in Firmicutes, Proteobacteria and Bacteroidetes phyla [35].…”
Section: The Effects Of Azithromycin On Airway Microbial Interactionsmentioning
confidence: 99%
“…Recent healthy murine studies show that lung communities clustered significantly by various environmental sources (vendors, cages and shipments) [3]. The exposure to elevated levels of PM 2.5 contributes to the change in sputum and pharyngeal microbiota composition, even in the healthy cohort [17,18].…”
Section: Introductionmentioning
confidence: 99%